Efforts to improve tajwid learning using the An-Nahdliyah method in Diniyah students - Mubarok, M. Zahid; Subandi, Mispani; Yusuf, Muhammad; Darmayanti, Rani (CV. BImbingan Belajar Assyfa, 2023)
The essential ability to read the Koran is critical for children, especially students. The information that the researchers obtained was that most of the students still had difficulty applying knowledge recitation, which he studied at the ustadz at the Darul Ulum Islamic Boarding School in Seputih Banyak. Matter the caused Lots factor Which influences include a lack of motivation to be able to read the Al-Qur'an fluently using correct recitation. In addition, para Students do not believe self And are Afraid of Wrong when they practice recitation in reading Al-Qur'an. The purpose of this research is to describe and analyse efforts to improve PAI learning on the main subject of Tajwid science using the An-Nahdliyah method in class V Ibtidaiyah Islamic boarding school students at the Darul Ulum Islamic Boarding School in Seputih Banyak, Central Lampung. This research is field research conducted on class V Ibtidaiyah Islamic boarding school students at the Darul Ulum Islamic Boarding School in Seputih Banyak, Central Lampung, in connection with efforts to improve PAI learning on the main subject of Tajwid using the An-Nahdliyah method. Researchers collect the data needed as a source of information using technique observation, interview, And documentation from data obtained, Then collected and processed so that a conclusion can be drawn. Based on the research results, it can be concluded that the method is fast responsive An-Nahdliyah, Which is applied in Madrasah Diniyah method An-Nahdliyah for the moment. This can overcome the difficulties of students and able to improve their ability to use the science of recitation, especially students of class V Madrasah Diniyah. Even though some students still experience difficulties applying the knowledge of recitation, the teachers continue to guide the children until they are fluent. The An-Nahdliyah method is an alternative method for dealing with children who have difficulty applying the science of tajwid by listening to and explaining to the child the mistakes they have experienced and correcting the reading.